Correlation Between Angiographic Features and Subtypes of Fusiform Aneurysm of Vertebral and Basilar Artery: Based On a Single-Institution Experience. Issue 2 (May 2015) - Shi, Wan-Yin; Li, Ming-Hua; Gu, Jian-Ping; Gu, Bin-Xian; Wang, Wu
Abstract : Objects: We retrospectively investigated the radiologic differences in subtypes of fusiform aneurysms (FA) of vertebral and basilar arteries. Methods: The study included 37 patients with 39 nonperipheral posterior circulation FAs detected by 3D-TOF-magnetic resonance angiography or by digital subtract angiography. Patient-specific and aneurysm-specific data were summarized. FAs were divided into 3 subtypes: focal FA (type I); classic dissecting aneurysm (type II); and dolichoectatic aneurysm (type III). Correlations between the subtypes and their angiographic features, including location, size, and rupture or not were analyzed. Results: Thirty-nine posterior FAs, including 28 aneurysms located at vertebral artery (VA), 8 at basilar artery (BA) and 3 at vertebrobasilar junction area, were detected in 37 patients. Twenty-one aneurysms in VA and 1 in BA were type II, among them 15 in VA and 1 in BA were ruptured. Focal FAs, including 7 in VA, 6 in BA, and 3 in vertebrobasilar junction area, were type I. One aneurysm in BA was type III. The subtypes of FAs were location specific ( P =0.002). Ruptured FAs seemed closely associated with intracranial segment of VA ( P =0.037). Conclusions: The subtypes of FAs were location specific, whereas ruptured FAs were mainly type II at VA without correlation with aneurysmal size.